Spiritual and ethical discourse of the sixties in Ukrainian dramaturgy of the 1960s–1980s - Matyushchenko, Angela (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The article examines the echoes of the moral and psychological intentions of the sixties' prose in Ukrainian dramaturgy of the 1960s–1980s, since in domestic science it is believed that the phenomenon of the sixties occurred primarily in the poetic and prose genres. Applying the historical and literary research method, based on the thesis of the destruction of the official military-victorious myth of the Second World War, first in O. Dovzhenko's film story "Ukraine in Fire", and later in the prose of the "children of war", in the process of comparative analysis of individual prose works of writers of the sixties and dramatic works of the most significant Ukrainian playwrights of the 1960s M. Zarudny and O. Kolomiyets, the author comes to the conclusion that in the 1960s one can rather observe discrepancies between the manifestation of realistic, mainly tragic-existential themes in Ukrainian prose and ideologically prolonged collisions in drama. Ukrainian dramaturgy of the 1960s – as the genre most ideologically engaged due to its ontological property of influencing the most mass audience through theatrical performance – was forced to balance between officially approved themes of "renewal of society of the Thaw era" and attempts to reflect processes of the revival of the moral and aesthetic primary sources of national existence and shift the focus of its attention to the human individuality with its true internal conflicts. However, in the next two decades, the best works of Ukrainian playwrights, and in particular M. Stelmakh, different in genre modifications and artistic properties, already in a unique way reflect the main philosophical and ethical dilemmas of the existence of a Ukrainian person, which so globally appeared in the works of H. Tyutyunnyk, E. Hutsal, V. Drozd.